2014
DOI: 10.1111/pim.12086
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against malaria after vaccination

Abstract: SUMMARYA good understanding of the immunological correlates of protective immunity is an important requirement for the development of effective vaccines against malaria. However, this concern has received little attention even in the face of two decades of intensive vaccine research. Here, we review the immune response to blood-stage malaria, with a particular focus on the type of vaccine most likely to induce the kind of response required to give strong protection against infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 108 publications
(147 reference statements)
1
16
0
Order By: Relevance
“…This type of responses, i.e., the activation of both Th1 and Th2 cells, is considered ideal for a blood-stage vaccine (Petritus and Burns, 2008;de Souza, 2014). Our findings on DNA prime/protein boosting have also indicated that among the DNA immunized groups, priming with DNA and boosting with protein clearly elevated the levels of all the cytokine in DNA/Protein group suggesting that DNA can prime the mice but itself is not sufficient enough to enhance the immune responses.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…This type of responses, i.e., the activation of both Th1 and Th2 cells, is considered ideal for a blood-stage vaccine (Petritus and Burns, 2008;de Souza, 2014). Our findings on DNA prime/protein boosting have also indicated that among the DNA immunized groups, priming with DNA and boosting with protein clearly elevated the levels of all the cytokine in DNA/Protein group suggesting that DNA can prime the mice but itself is not sufficient enough to enhance the immune responses.…”
Section: Discussionmentioning
confidence: 39%
“…In the present study, priming with P. Previous studies have shown that cell mediated immune responses, in addition to antibody responses, are required for protection against malaria Sedegah et al, 1998;de Souza, 2014). Present study on measuring T cell responses in mice after DNA immunization and protein boosting exhibited that T cell proliferation was significantly enhanced in DNA/Protein and Protein/Protein groups.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The main challenges to a blood stage vaccine development include, but are not limited to, selecting an antigen that is both essential and elicits a strong, protective immune response, yet is not so diverse that immunity to only the vaccine strain would develop, and presenting the antigen to the host immune system with a sufficiently immunogenic but safe vaccine adjuvant, the availability and suitability of animal models, as well as gaps in our knowledge of the nature of antimalarial immunity and how it is acquired. 109,110 The malaria antigen RH5 described in this review may well live up to this challenge. …”
Section: Future Challenges or Closing Remarksmentioning
confidence: 96%